Baseline sputum eosinophil + neutrophil subgroups’ clinical characteristics and longitudinal trajectories for NHLBI Severe Asthma Research Program (SARP 3) cohort - Hastie, Annette T.; Mauger, David T.; Denlinger, Loren C.; Coverstone, Andrea; Castro, Mario; Erzurum, Serpil; Jarjour, Nijar; Levy, Bruce D.; Meyers, Deborah A.; Moore, Wendy C.; Phillips, Brenda; Wenzel, Sally E.; et al. (Journal of allergy and clinical immunology, 2020)
Combined elevated sputum eosinophils+neutrophils in asthma associated with lowest lung function, greater healthcare utilization, and longitudinally, further spirometric loss, implicating cell-cell interactions or overlapping inflammatory pathways while increased eosinophils or neutrophils alone show less effect.